2018
DOI: 10.1016/j.ijscr.2018.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Unusual complication of seroma after ventral hernia mesh repair: Digestive perforation by tacks. A case report

Abstract: HighlightsComplicated seromas are rare and can cause therapeutic problems.The right timing for mesh removal is delicate to be detected.Erosion of the small bowel by the tacks has been reported. It seems to be due to technical problems.In our case the pressure exerted by the bulky seroma favored the fistulization of the small bowel.This case suggests that the type of mesh fixation may influence the time of its removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
2
1
1
Order By: Relevance
“…Relationship between perforation and vascular complications was also previously reported 2 . It is very rare that the use of mesh causes GIP 15 . However, in our study, the use of mesh was found to be significantly higher in patients that develop perforations.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Relationship between perforation and vascular complications was also previously reported 2 . It is very rare that the use of mesh causes GIP 15 . However, in our study, the use of mesh was found to be significantly higher in patients that develop perforations.…”
Section: Discussionsupporting
confidence: 78%
“…2 It is very rare that the use of mesh causes GIP. 15 However, in our study, the use of mesh was found to be significantly higher in patients that develop perforations. In the literature, we did not find any study investigating the relationship between development of GIP after liver transplantation and mesh usage.…”
Section: Discussioncontrasting
confidence: 63%
“…Among these complications, seroma development and wound infection were the most frequently reported types. The results presented in this study align with prior research that has identified seroma development and wound infection as the most prevalent problems observed in hernia repair procedures [ 26 - 27 ]. The study findings suggest that the relatively low occurrence of problems can be related to several factors, such as the high level of proficiency exhibited by the surgical team, the utilization of acceptable surgical procedures, and the adherence to perioperative care standards.…”
Section: Discussionsupporting
confidence: 90%
“…While mesh repair is recommended regardless of open or laparoscopic technique, the large abdominal disruption in our patient warranted combination of biological and synthetic mesh [ 8 ]. Biological meshes provide the benefit of bridging abdominal wall defects and are less prone to infection, enterocutaneous fistula formation, and adhesion formation; however, they confer less mechanical support than synthetic counterparts [ 9 , 10 ]. In this case, we used a combination of both biological mesh and synthetic Ventralight ST mesh.…”
Section: Discussionmentioning
confidence: 99%